Research on Climate Governance Provisions in International Investment Treaties - Yu, Yunda (International Journal of Social Sciences and Public Administration, 2025)
The climate governance models involved in international investment law are mainly divided into three types: the hard law approach, the soft law approach, and the approach that combines both hard and soft law. Each of these approaches offers solutions to different climate governance issues in international investment.This paper argues that the crux of the climate governance challenges in international investment lies in the conflict between the economic value of efficiency and the international public principle of efficiency. According to international practice, the reasons for the differences in climate governance models in international investment include the pluralism of legal interpretation, the fragmentation of treaties and other international documents, and the differences in the construction of legitimacy and legality.This paper believes that state actors can address the conflict between the legitimacy and legality of climate protection clauses in international investment by establishing a dual path of “hard law and soft law” through international cooperation.